The Mpondo Revolt 1960 - Copelyn, J. (My University, 1974)
In accounting for the growth of militancy in Eastern Pondoland in I960, it is necessary to analyse a number of changes enforced in the reserves by the Government in the 1950's. Most prominent of these are the intensification of 'betterment' schemes and the institution of the Bantu Authorities system of local government. This section of the paper then, is largely concerned with radical critique of these two pillars of rural administration
African Studies Seminar series. Paper presented June, 1974
Keywords: Mpondo revolt; Pondoland (South Africa). Politics and government